2013
DOI: 10.1111/gcb.12122
|View full text |Cite
|
Sign up to set email alerts
|

Regional zooplankton dispersal provides spatial insurance for ecosystem function

Abstract: Changing environmental conditions are affecting diversity and ecosystem function globally. Theory suggests that dispersal from a regional species pool may buffer against changes in local community diversity and ecosystem function after a disturbance through the establishment of functionally redundant tolerant species. The spatial insurance provided by dispersal may decrease through time after environmental change as the local community monopolizes resources and reduces community invasibility. To test for evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 40 publications
1
41
3
Order By: Relevance
“…The same pattern of rising salinity levels during periods of draught can be found for other lakes on the Great Plains, with some reaching values >20 g/L (Laird et al, 1998;Michels et al, 2007). In addition, past studies have shown that dispersal can be important for maintaining community structure and function in the face of environmental change (Cottenie & De Meester, 2004;Strecker & Arnott, 2010;Thompson & Shurin, 2012;Symons & Arnott, 2013). Although we were unable to reach firm conclusions about the role of dispersal in our study, our results suggest that dispersal may allow cladocerans to persist in lakes experiencing moderate salinity increases.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The same pattern of rising salinity levels during periods of draught can be found for other lakes on the Great Plains, with some reaching values >20 g/L (Laird et al, 1998;Michels et al, 2007). In addition, past studies have shown that dispersal can be important for maintaining community structure and function in the face of environmental change (Cottenie & De Meester, 2004;Strecker & Arnott, 2010;Thompson & Shurin, 2012;Symons & Arnott, 2013). Although we were unable to reach firm conclusions about the role of dispersal in our study, our results suggest that dispersal may allow cladocerans to persist in lakes experiencing moderate salinity increases.…”
Section: Discussionsupporting
confidence: 59%
“…As a result, the magnitude of the salinity changes tested in previous studies were quite small (<1 g/L), paling in comparison to the spatial and temporal heterogeneity in salinity levels experienced for prairie lakes (Symons & Arnott, 2013;Thompson & Shurin, 2012). As a result, the magnitude of the salinity changes tested in previous studies were quite small (<1 g/L), paling in comparison to the spatial and temporal heterogeneity in salinity levels experienced for prairie lakes (Symons & Arnott, 2013;Thompson & Shurin, 2012).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Increased nutrient loading and reduced dispersal rates owing to fragmentation are amongst the major drivers of species extinctions worldwide and can undermine ecosystem functioning and stability both in terrestrial and aquatic systems (Kruk et al 2009, Symons and Arnott 2013, Hautier et al 2015, Hooftman et al 2015. Our study additionally suggests that nutrient loading and dispersal limitation synergistically enhance each other's effects on ÎČ-diversity.…”
Section: Discussionmentioning
confidence: 57%
“…Recent definitions of resilience encompass aspects of both recovery and 84 resistance, although different mechanisms can underpin these, and in some cases there 85 might be trade-offs between them [24]. However, some mechanisms can promote both 86 resistance and recovery depending on the timeframe in which a system is observed (e.g. 87 very rapid recovery can look like resistance).…”
mentioning
confidence: 99%